(untitled) - Hoover, John (Hoboken, N.J., 2006)
Selling to customers looking to get the most bang for their buck is a difficult feat. The only customers tougher than hagglers are the ones so uninformed about what they are buying, they don't even realize when they are getting the deal of a lifetime. In How to Sell to an Idiot, authors John Hoover and Bill Sparkman show you how to ignore your own inner idiot and start selling more by doing less of what doesn't work and more of what does. Along with a wealth of proven sales guidance and effective techniques.
Keywords: Selling,Bán hàng; Psychological aspects,Khía cạnh tâm lý